Relasi Kompensasi dengan Produktivitas kerja Studi Kasus PT. Asuransi Jiwasraya (Persero) - Anggraini, Dewi; Sutarno, Sutarno (Politeknik Cendana, 2020)
Compensation is all in the form of money, direct or indirect goods received by employees in return for services provided by the company. According to Sutrisno (2009), productivity is generally defined as the relationship between output (goods or services) and inputs (labor, materials, money). Indicators of compensation are fair, fair, and reasonable. While indicators of work productivity are ability, increasing the results achieved, work spirit, self-development, quality, and efficiency. This study uses a non-probability sampling technique with saturated sampling, with 30 samples at PT. BNI Life Insurance (Persero) Medan. The results of the correlation coefficient test showed that the rxy value was 0.359. According to Arikunto (2010) criteria for the relation category of correlation coefficient (r) 0,200-0,400 (low). While the direction of the relationship is positive because the value of r is positive, it means that the better the welfare of employees the more work productivity of employees of PT. Asuransi Jiwasraya (Persero) Medan. Test the coefficient of determination between compensation and work productivity of 12.9% and the remaining 87.1% is influenced by factors other than compensation. then the result of t arithmetic is 2.036, the result of the t table is 2.05. T arithmetic <t table is 2.036 <2.05 so that Ho is accepted and Ha is rejected, it can be concluded that there is no relationship between compensation and work productivity.